1, 4-Bis(imidazole)butane ligand and strontium(ii) directed 1-D chains based on basket-type molybdophosphates and transition metal (TM) linkers1. Issue 32 (28th August 2015) - Zhang, He; Lv, Jing-Hua; Yu, Kai; Wang, Chun-Mei; Wang, Chun-Xiao; Wang, Lu; Zhou, Bai-Bin
<x xml:space="preserve">Abstract</x> Five isostructural 1-D chains based on P6Mo18O73 and {TM(H2O)2}, show good degradation ability for typical dyes under UV light and bifunctional electrocatalytic behaviors for oxidation of AA and reduction of NO2−.